Charakter a vitalita frazeológie východoslovenskej variety rómčiny vybraných literárnych textov - Koptová, Martina (Romano džaniben, 2011)
The article describes the character and vitality of phraseology of Romani language, (especially the eastern Slovak form of the northern central dialect) in selected literary texts. Special attention is paid primarily to the following fields: identification of phraseologisms, description of properties, categorization, problems with translation, and specification of the vitality of phraseologisms. The phraseological research of literary texts has shown that the diversity of Romani phraseology is comparable with Slovak language. Moreover, we can also find relatively high amount of related phraseologisms in both Slovak and Romani language. Considerable tendency has occurred in Romani in calquing the phraseologisms from majority language. Questionnaire research among native Romani speakers has shown that respondents were familiar with phraseologisms excerpted from the literature but mainly passively. The hypothesis that older respondents would be more familiar with these phraseologisms has not been affirmed. The students of one grammar school were most familiar with submitted phraseologisms because they have come into contact with them during their studies, which shows how important it is to improve Romani language education at school in order to preserve phraseological richness of Romani language. Keywords: phraseology, phraseologisms, Romani language, Romani literature, categorization of phraseologisms, identification of phraseologisms, translation of phraseologisms, specification of the vitality of phraseologisms.